2017
DOI: 10.1007/s11682-017-9682-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the up’s and down’s of emotion regulation in lifetime depression

Abstract: Reappraisal is a particularly effective strategy for influencing emotional experiences, specifically for reducing the impact of negative stimuli. Although depression has repeatedly been linked to dysfunctional behavioral and neural emotion regulation, prefrontal and amygdala engagement seems to vary with clinical characteristics and the specific regulation strategy used. Whereas previous neuroimaging research has focused on down-regulating reactions to emotionally evocative scenes, the current study compared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In the present study, the path of the relationship between emotion regulation difficulty and depression is significant and positive; that is consistent with researches of Berkking et al (19), Folk et al (20), Joormann (21), Radke et al (22) and Schäfer et al (31). In fact, the results of this study showed that emotion regulation difficulty is known as an important factor for depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the path of the relationship between emotion regulation difficulty and depression is significant and positive; that is consistent with researches of Berkking et al (19), Folk et al (20), Joormann (21), Radke et al (22) and Schäfer et al (31). In fact, the results of this study showed that emotion regulation difficulty is known as an important factor for depression.…”
Section: Discussionsupporting
confidence: 93%
“…Students, who use inappropriate emotion regulation strategies, cannot afford to control their own living conditions in stressful situations and academic environments; therefore, they become depressed because of helplessness. Research of Berking, Wirtz, Svaldi and Hofmann (19), Folk, Zeman, Poon and Dallaire (20), Joormann and Vanderlind (21) and Radke et al (22) showed that the emotion regulation difficulty plays an important role in the starting and recurrence of depression disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional social behavior in depression ( Hirschfeld et al, 1999 ) calls for investigating and applying emotion regulation in interpersonal interactions ( Radke et al, 2018 ). Facial emotions are an important component of social communication, and therefore have a high ecologic validity and offer an ideal possibility to investigate emotion regulation in social situations.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, participants were asked how difficult the task was and how much effort they put into the task. A similar design has been successfully implemented in a previous study ( Radke et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, in highlighting the relevance of load theory in advancing our understanding of attentional control as it relates to psychological health, we and others have shown that individual differences in the anxiety spectrum (e.g., trait anxiety, social anxiety disorder) and traits that act as a vulnerability factor to anxiety and depression (e.g., behavioral inhibition; Muris, Merckelbach, Schmidt, Gadet, & Bogie, 2001) are frequently observed when perceptual load is low (Bishop et al, 2007; Bunford, Roberts, et al, 2017; Wheaton et al, 2014). It has also been demonstrated that anxious and depressed individuals exhibit aberrant neurofunctional activity during cognitive reappraisal to negative stimuli (Fitzgerald et al, 2017; Goldin, Manber, Hakimi, Canli, & Gross, 2009; Radke et al, 2017; Stephanou, Davey, Kerestes, Whittle, & Harrison, 2017). Furthermore, neural activity (i.e., ACC, amygdala) during reappraisal and to negative distractors under low (relative to high) perceptual load conditions predicts symptom change after cognitive behavioral therapy (CBT) in socially anxious patients (Klumpp, Fitzgerald, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%